Perbedaan Terapi Rendaman Air Hangat Campur Garam dan Rendaman Air Hangat Campur Kencur Untuk Penurunan Edema Kaki Pada Ibu Hamil TM III - Jamilah Jamilah; Retno Hilmi Suryaningtyas (Jurnal Ners, 2025)
Edema or swelling of the legs is one of the complaints frequently experienced by pregnant women, especially in the third trimester. If not treated properly, this condition can cause discomfort for pregnant women and, in some cases, risks causing further complications. Traditional healing practices to reduce leg swelling have many methods, one of which is soaking in warm water mixed with salt and warm water mixed with galangal. This study aims to determine the difference between warm water immersion therapy mixed with salt and warm water immersion mixed with galangal to reduce leg edema in TM III pregnant women. This type of research is pre-experiment with one group pretest posttest design. Data collection was carried out using primary data, namely data obtained from observation. The data collection instrument used was an observation sheet. Hypothesis testing uses the Wilcoxon Test and Mann Whitney Test because the data is not normally distributed. The population of this study was 44 TM III pregnant women with leg edema. There were 22 respondents from TM III pregnant women with edema who were treated with warm water baths mixed with salt, while 22 respondents from TM III pregnant women with edema were treated with warm water baths mixed with galangal. Edema of TM III Pregnant Women Before and After Soaking in Warm Water Mixed with Salt and Soaking in Warm Water Mixed with Galangal, there are differences that can be seen starting from day 6 and day 7 with a significance value of 0.001 (< 0.05).TM III pregnant women with edema in the legs experienced a faster reduction in edema by soaking in warm water mixed with galangal than by soaking in warm water mixed with salt.